2014
DOI: 10.5194/acp-14-12291-2014
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of HCHO and CHOCHO at a semi-rural site in southern China during the PRIDE-PRD2006 campaign

Abstract: Abstract. HCHO and CHOCHO are important trace gases in the atmosphere, serving as tracers of VOC oxidations. In the past decade, high concentrations of HCHO and CHOCHO have been observed for the Pearl River Delta (PRD) region in southern China. In this study, we performed box model simulations of HCHO and CHOCHO at a semi-rural site in the PRD, focusing on understanding their sources and sinks and factors influencing the CHOCHO to HCHO ratio (R GF ). The model was constrained by the simultaneous measurements o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 48 publications
(92 reference statements)
8
66
0
Order By: Relevance
“…More specifically, as indicated in Figure S6, the higher mixing ratio of HCHO was found associated with higher temperature while RH and wind field had a minor impact during the day in Shenzhen, which provides further evidence for the photochemical origin of HCHO. The discrepancy between summer and winter is not as prominent as that in other inland cities, which may be associated with the relatively smaller temperature difference and the unfavorable vertical diffusion conditions in the PRD in winter (Guo et al, ; X. Huang et al, ).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…More specifically, as indicated in Figure S6, the higher mixing ratio of HCHO was found associated with higher temperature while RH and wind field had a minor impact during the day in Shenzhen, which provides further evidence for the photochemical origin of HCHO. The discrepancy between summer and winter is not as prominent as that in other inland cities, which may be associated with the relatively smaller temperature difference and the unfavorable vertical diffusion conditions in the PRD in winter (Guo et al, ; X. Huang et al, ).…”
Section: Resultsmentioning
confidence: 86%
“…Measurement techniques of atmospheric HCHO have rapidly developed in the past decade (Hak et al, ; Ho et al, ; Li et al, ), among which the method of 2,4‐dinitrophenylhydrazine followed by high‐performance liquid chromatography (Pang & Mu, ; Shao et al, ; Wang et al, ), fluorometry based on a diffusion scrubber and the Hantzsch reaction (Li et al, , ; M. Li et al, ), differential optical absorption spectroscopy (X. Li et al, , ), infrared absorption (Wert et al, ), and laser‐induced fluorescence (Cazorla et al, ; Hottle et al, ) are popular methods to measure HCHO. Proton transfer reaction‐mass spectrometry (PTR‐MS) is a relatively novel method that can be employed for fast measurements of HCHO and other OVOCs simultaneously (Inomata et al, ; Karl et al, ; Steinbacher et al, ; Zheng et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NO 2 is high but less than in the East China Plain. As pointed out previously by Liu et al (2012) and Li et al (2014), the unusually high CHOCHO concentrations over the PRD can be attributed to high emissions of aromatic VOCs.…”
Section: Methodsmentioning
confidence: 85%
“…For example, a recent model study at a semi-rural site in southern China by Li et al (2014) showed 2-5 times higher HCHO than observations. On the other hand, underpredictions have also been found in a few studies (Ayers et al, 1997;Jaegle et al, 2000;Weller et al, 2000;Kormann et al, 2003).…”
mentioning
confidence: 92%